A Lexical Learning Case Study of Multimodality Discourse Analysis (Contemporary Education and Teaching Research, 2026)
The contemporary era of information technology has given rise to a novel approach to word retention: the utilisation of English vocabulary memory applications. With the support of mobile devices, English vocabulary memory applications have realised the convenience of word memorisation and attracted many users. The integration of multimodal theory into digital vocabulary applications has become an increasingly interesting topic in social science. However, limited research has explored systematic multimodal discourse analysis to examine the semantic construction through a complex interaction of different resources. The current study conducted a multimodal analysis of an English vocabulary memory application (No Need to Memorise Words) and analysed its functions to explore the use of multimodal means. The study employed the methodology of questionnaires to examine the overall perception of college users towards the APP and their evaluation of the multimodal means utilised in the application. The research and survey evaluated the effectiveness of multimodal means for word memorisation from both scientific and practical levels. Through the specific case study, the research investigated the APP’s multimodal design across key learning activities. The analysis results showed that this APP mobilises users’ auditory and visual senses, and facilitates word memorisation in both visual and auditory modalities through various means and resources, such as text, images, and sounds. The findings also show that this APP has a wide audience and its simple operation, as well as functions combined with multimodal means, effectively promoted word memory. The study contributes to the literature on multimodal learning strategies by providing a comprehensive analysis of how multimodal resources construct meaning in vocabulary learning. In addition, practical implications are also discussed for pedagogy applications.